2018
DOI: 10.1038/s41598-018-33382-2
|View full text |Cite
|
Sign up to set email alerts
|

An innovative flow cytometry method to screen human scFv-phages selected by in vivo phage-display in an animal model of atherosclerosis

Abstract: Atherosclerosis is a chronic, progressive inflammatory disease that may develop into vulnerable lesions leading to thrombosis. This pathology is characterized by the deposition of lipids within the arterial wall and infiltration of immune cells leading to amplification of inflammation. Nowadays there is a rising interest to assess directly the molecular and cellular components that underlie the clinical condition of stroke and myocardial infarction. Single chain fragment variable (scFv)-phages issuing from a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…In an in vivo phage display screen, animals are euthanized and perfused after the desired time point (~5–10 min for identifying phage specific for endothelium, or ~4–6 hr for identifying phage specific for cells within a desired tissue) following i.v. administration and phage is recovered from the tissue or a section of tissue by homogenizing and amplifying in Escherichia coli (Siva Sai Krishna Dasa et al, 2015; Deramchia et al, 2012; Gutknecht et al, 2017; Hemadou et al, 2018). Target specific phage is amplified in bacteria, and by doing additional rounds of selection, high affinity phage clones can be obtained.…”
Section: Future Directionsmentioning
confidence: 99%
“…In an in vivo phage display screen, animals are euthanized and perfused after the desired time point (~5–10 min for identifying phage specific for endothelium, or ~4–6 hr for identifying phage specific for cells within a desired tissue) following i.v. administration and phage is recovered from the tissue or a section of tissue by homogenizing and amplifying in Escherichia coli (Siva Sai Krishna Dasa et al, 2015; Deramchia et al, 2012; Gutknecht et al, 2017; Hemadou et al, 2018). Target specific phage is amplified in bacteria, and by doing additional rounds of selection, high affinity phage clones can be obtained.…”
Section: Future Directionsmentioning
confidence: 99%
“…Identification of relevant biomarkers is the stepping stone for an efficient molecular imaging using different modalities. Recent studies highlight the capacity of combining in vivo phage display (using a human combinatorial antibody library) and high-throughput biological screening on atheroma extracts 187 and/or in silico tracking of the most frequently used antibody sequences 188 to select potent and valuable antibody candidates. Further characterization of the targeted molecules by proteomic approaches would give new insights into in vivo targetable, upregulated biomarkers of atherosclerosis.…”
Section: Resultsmentioning
confidence: 99%
“…P3 specifically targets galectin-3, a protein that has been highlighted in recent studies as a new atherosclerosis biomarker [ 55 ]. P3 was discovered by in vivo phage-display selection in an animal model of atherosclerosis using a human scFv library [ 56 , 57 ]. Its ability to target galectin-3 within atherosclerotic lesions has been demonstrated in vitro and ex vivo (patent WO2019068863A1).…”
Section: Discussionmentioning
confidence: 99%
“…IHC experiments were performed as previously described [ 31 ]. Briefly, after deparaffinization, heat-induced epitope retrieval and non-specific interaction blocking, as described in [ 56 ], aorta sections were incubated with NE-P3 ((#5), 53 µg/mL of P3 antibody, 158 mg/L of Fe), unconjugated NE–PEG 3400 –maleimide ((#3), 158 mg/L of Fe), ScFv-Fc-2Cys P3 HuAb (53 µg/L) (positive control), or the diluent alone (negative control) overnight. This was followed by incubation with the secondary HRP-conjugated goat anti-human antibody (Fcγ-specific; 1:1000 ( v / v ) (Jackson ImmunoResearch; West Grove, PA, USA), and antibody binding was revealed using the Dako Liquid DAB+ Substrate Chromogen System (Agilent Technologies Inc, Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%